The potential of global positioning system in weather and environmental studies - Yahya, Mohd. Hafiz (2008)
Malaysia is witnessing a rapid growth in the vicinity of urban cities with the construction of large engineering structures (e.g. towers, factories, high-rise condominiums, wide-span bridges and highways) to meet the requirement for the nation’s economic growth, societal activities and the aspirations of its population. These manmade structures are, however, subject to deformation and structural displacement caused by severe weather conditions such as strong wind, fluctuating temperatures, seasonal monsoons, flash flooding and heavy rains. This paper gives an overview of the role of Global Positioning System (GPS) technology, in retrieving atmospheric parameters for monitoring and predicting severe weather conditions. As GPS technology is still relatively new to the Malaysian weather forecasting community, the principles presented in this paper deal with the two main approaches: the ground-based atmospheric sounding and the radio occultation method. If appropriate strategies are employed during the data acquisition and data processing phases, it is noted that GPS is potentially capable of being implemented as an alternative and promising tool to remotely sense the spatial and temporal variability of the Earth’s atmosphere. Because of its practicality, accuracy and data continuity, GPS is adequate and effective in overcoming the shortcomings of other commonly-used atmospheric sounding techniques.